Maxillary distalization by a rearrangement of the Leaf Expander® screw combined with palatal miniscrews: A case report on the MaXimo Appliance - Perinetti, Giuseppe; Bruno, Alex; Tonini, Paolo (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: This case report describes the treatment of a crowded dental Class II malocclusion in 13 years, 2 months female patient. Maxillary distalization was achieved by a novel compliance-free appliance referred to as MaXimo, which was built by a rearrangement of the Leaf Expander® screw having palatal miniscrews as the anchorage core. Case Presentation: Pre-treatment, post-treatment and 1-year follow-up records are shown. No side effects, breakage of the appliance or loss of miniscrews was encountered. The active distalization phase lasted 14 months, while the whole treatment, including the use of multibrackets appliance, lasted 25 months. A significant spontaneous distal drifting of the premolars and canines was seen. The treatment outcomes proved to be stable at the follow-up with acceptable aesthetic and functional results.Conclusion: The MaXimo appliance proved to be efficient and of easy management, and its use may be recommended when distalization of the maxillary dentition is required. Being mostly assembled by the manufactured, the MaXimo appliance is also cheap and of easy construction.